Pengaruh Model Pembelajaran PAKEM Terhadap Prestasi Belajar Matematika Siswa Kelas V SDN Pondok Kelapa 05 Pagi Jakarta - Alberth Supriyanto Manurung; Abdul Halim (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
The purpose of this study was to determine the effect of an effective and fun creative active learning model on the mathematics learning outcomes of grade V elementary school students. The research method used was a survey method and used simple correlation and regression analysis techniques, multiple regression and correlation. This research was conducted at SDN Pondok Kelapa 05 Pagi Jakarta, using the cluster sampling technique. Based on this research, it is expected that the mathematics learning outcomes of fifth grade elementary school students can be improved by using active creative learning model that is effective and fun to be significant determinants. Based on the t-test analysis, it was obtained that t count was 2.61 and t table was 1.69 meaning that there was a positive contribution between the active, creative, effective and fun learning model variables and the learning outcomes of mathematics because tcount> t table was 2.61> 1.69. The coefficient of determination is 0.1672, which explains that 16.72% of the variance of the mathematics learning achievement variable is explained or determined by the active creative learning model which is effective and fun. Thus, it can be concluded that the creative active learning model approach is effective and fun to improve mathematics learning achievement.